Mild behavioral impairment and its relationship to cognition in community‐dwelling older adults from the Boston Latino Aging Study - Jorge Alcina; Diana Munera; Lusiana Martinez; Averi Giudicessi; Nikole A. Bonillas Félix; Randy Medrano; Jairo E. Martinez; Isabel Solis; Catarina Tristão‐Pereira; Vincent Malotaux; Bing He; Alexandre Ribas; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract Background Mild behavioral impairment (MBI) is associated with cognitive decline and dementia risk. This study assessed the relationship between MBI severity and cognition in community‐dwelling older Latino adults. Methods The cognitive function index (CFI) assessed subjective cognition, and the MBI‐Checklist (MBI‐C; self‐report) measured MBI symptoms in 168 older Latinos (134 cognitively unimpaired, 34 with mild cognitive impairment). The Mini‐Mental State Examination (MMSE) and NEUROPSI Delayed Word List Recall measured cognitive function. Linear regressions examined the impact of MBI‐C symptoms on cognition, controlling for age, sex, and education. Results The MBI domain of decreased motivation predicted subjective cognition and delayed verbal recall performance. The mood dysregulation domain predicted only subjective cognition. Neither domain predicted total MMSE scores. Discussion MBI symptoms of decreased motivation and mood dysregulation influenced poorer subjective and objective cognition in Latinos, potentially signaling prodromal Alzheimer's related changes. These findings highlight the need to assess neuropsychiatric symptoms in this population. Highlights Decreased motivation predicted worse subjective cognition and verbal memory. Mood dysregulation only predicted worse subjective cognition. These findings were adjusted for age, sex, and education in Latino older adults.